Western Psychiatry and Traditional Healing: Postcolonial Perspectives - Tony B. Benning, Dr. (International Journal of Psychosocial Rehabilitation, 2015)
This review takes as its starting point the chasm separating Western psychiatry from the indigenous healing traditions−es- pecially in the North American context. The principle arguments of this paper are twofold: that this state of affairs is un- likely to change unless there is a greater understanding of the sorts of factors that are underpinning and perpetuating this chasm and secondly, that indispensable to this understanding, is a perspective that takes into consideration the way in which Western psychiatry has historically related to and continues to relate to the indigenous world in a manner that repro- duces and reinforces colonial values. A greater awareness of the enduring impact of colonialism and its legacies promises to illuminate the problematic nature of the relationship between Western psychiatry and indigenous or traditional systems of healing.